IMPLEMENTASI BIOSLURRY SEBAGAI PUPUK ORGANIK UNTUK MENDUKUNG KETAHANAN PANGAN DAN PENGELOLAAN LIMBAH BERKELANJUTAN - Harmayani, Ria; Fitriyah, Abyadul; Alimuddin; Risfiyanty, Dwi Kartika; Alyaminy, Humaidatul Aminah Zaim (Fakultas Pertania Universitas Muara Bungo, 2025)
Food security and organic waste management are major challenges in the modern era that require sustainable and environmentally friendly solutions. Bioslurry, a nutrient-rich fermented liquid from organic waste, emerges as an innovation to support waste management while enhancing agricultural productivity. This community service activity aims to increase public awareness and capacity to produce and utilize bioslurry independently from household and agricultural waste, thereby supporting food security and sustainable waste management. Through training and demonstrations over a period of 7-14 days using EM4, the community is taught the fermentation process and the application of bioslurry as an organic liquid fertilizer. Evaluation results show an increase in knowledge, adoption of simple technology, and economic and environmental benefits. As a result, community members are able to produce bioslurry independently, which is then used to fertilize crops such as tomatoes and chili peppers, leading to a yield increase of 20-30%. Additionally, this activity contributes to reducing the volume of organic waste polluting the environment, increasing farmers’ income, and strengthening local policies on sustainable waste management. Overall, this activity successfully improved awareness, knowledge, and practices in sustainable organic waste management, providing economic, social, and environmental benefits to the target community.